A comparative handbook to the Gospel of Mark : comparisons with Pseudepigrapha, the Qumran Schrolls [sic], and Rabbinic literature - Chilton, Bruce.; Bock, Darrell L.; Gurtner, Daniel M. (The New Testament Gospels in their Judaic Contexts, 2010)
This comparative handbook is intended to provide scholars of the New Testament with detailed, systematic and accurate resources concerning the Judaic context of the gospel of Mark. It aims to serve as a powerful tool to assist the reader - and commentator - in understanding and commenting on the gospel of Mark. Introductions are provided to help with issues of dating and the development of the literatures concerned. Possible interpretations are also presented, where suitable.